Implementation of Circular Business Models in Construction and Demolition Waste Management of India - Jaya Surya R; Dr. Kranti Kumar M (International Journal of Engineering and Management Research, 2021)
In the world, around 30% of the total solid waste is construction and demolition waste. In India, as per the building material promotion council, 150 million tonnes of C&D waste is generated every year. In the total C&D waste, only one percent which is 6500 tonnes per day is recycled, mentioned in the report released by the Centre for science and environment, New Delhi. There is a rising gap between increasing demand and limited sources in the construction sector of India. It leads to market instability and environmental harm. Linear business model is most commonly used in present times. It is one of the main reasons for the increase of C&D wastes. This linear approach (source-commodity-waste) encourages the one-use of products. It leads to excessive dumping of C&D wastes in landfills, which is not a sustainable practice. Circular business models leads to closed-loop approach (source-commodity-waste-new source). The adoption of circular business models in C&D waste management is the possible solution for the decreasing resources. This study aims to discuss the implementation of various approaches including conceptual models, methods, and tools of circular business models in the C&D waste management in India, which leads to the circular economy and sustainable development. Through the study of recent literature sources, various data related to circular business models, circular economy are collected. Data analysis will be done using the literature review. This research will highlight the socio-economic, environmental benefits, improvements, and the applicability of circular business models in the C&D waste management of India. This paper is concluded that framing strict circular economy policies for India would encourage the implementation of CBM in C&D waste management which reduces the need for fresh resources and ensures sustainable development.